2018
DOI: 10.1177/0093854818784988
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of the MAYSI-2 and PAI-A for Suicide-Related Behavior and Nonsuicidal Self-Injury Among Adjudicated Adolescent Offenders on Probation

Abstract: Suicide-related behavior (SRB), defined as any behavior undertaken with the deliberate intent to end life (e.g., plans, attempts, completed suicide), and non-suicidal self-injury (NSSI), defined as any self-destructive behavior undertaken to damage or harm oneself without the intention of dying (e.g., cutting, burning, biting; Nock, Joiner, Gordon, Lloyd-Richardson, & Prinstein, 2006), are major health concerns among justice-involved youth (Dixon-Gordon, Harrison & Roesch, 2012; Hayes, 2004). SRB and NSSI amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Butler et al (2007) found that scores in the Caution/Warning range on the Angry-Irritable, Somatic Complaints, Depressed-Anxious, and SI scales of the MAYSI significantly predicted placement on suicide watch of adjudicated male youth at a residential treatment center. However, other research assessing nonincarcerated youth indicated that the MAYSI-2 subscales at initial screening were not predictive of future suicidal behaviors, though clinically significant SI and Thought Disturbance scores did predict NSSI at 3-month follow-up for youth on probation (Shaffer et al, 2018).…”
Section: Introductionmentioning
confidence: 83%
“…Butler et al (2007) found that scores in the Caution/Warning range on the Angry-Irritable, Somatic Complaints, Depressed-Anxious, and SI scales of the MAYSI significantly predicted placement on suicide watch of adjudicated male youth at a residential treatment center. However, other research assessing nonincarcerated youth indicated that the MAYSI-2 subscales at initial screening were not predictive of future suicidal behaviors, though clinically significant SI and Thought Disturbance scores did predict NSSI at 3-month follow-up for youth on probation (Shaffer et al, 2018).…”
Section: Introductionmentioning
confidence: 83%
“…In terms of mental health, acute stress has been associated with higher rates of suicidality, but was not the sole variable impacting the likelihood of suicide attempts (López-Díaz et al, 2018). In addition to the gap in physical health services, studies show that individuals on parole often lack mental health services aimed at addressing suicide-related behaviors, non-suicidal self-injury, and a multitude of behavioral health concerns (Bryson et al, 2019;Houser et al, 2019;Shaffer et al, 2018;Timmer & Nowotny, 2021;Van Deinse et al, 2019). For example, some estimates suggest that as many as 29% of persons on parole experience risk factors associated with suicide, such as depression, psychological distress, and episodes of major depression (Bryson et al, 2019;Visher & Courtney, 2007;Yu et al, 2014).…”
Section: Physical/mental Health and Suicide Ideation Planning And Att...mentioning
confidence: 99%
“…Also, while the dichotomized measures of mental health problems and suicide risk do not reflect the complexity of the problem, the findings of the study show that the PACT may be a good screening tool to identify a need for a psychiatric evaluation. Future studies should test construct and predictive validity of the PACT in screening suicidal ideation and behaviors in comparison with other suicide-specific screening tools such as the Suicide Behavior Questionnaire [40].…”
Section: Limitationsmentioning
confidence: 99%